Promoting Strategies Towards Gender Equality in Private Higher Education in Klang Valley, Malaysia (Architecture Image Studies, 2026)
Gender inequality in higher education, particularly within leadership roles, remains a significant issue globally and in Malaysia. Despite the increasing enrolment of women in higher education, there is a stark underrepresentation of women in academic and administrative leadership positions. This research investigates the factors contributing to gender disparities in private higher education institutions in Malaysia, focusing on institutional policies, cultural and societal norms, and socioeconomic barriers. The study utilizes a quantitative methodology, employing a validated questionnaire distributed to 389 students across private institutions in Malaysia to assess their perceptions of gender equality. The analysis revealed that institutional policies and governance, socioeconomic factors, cultural norms, professional development, and mentorship programs significantly influence gender equality in higher education. Among these, socioeconomic factors were found to have the strongest positive impact, while leadership representation and mentorship programs had a negative correlation, indicating the need for more comprehensive and inclusive support structures. The study highlights the critical role of institutional frameworks and societal attitudes in bridging the gender gap in academia and calls for targeted reforms to foster gender equality in Malaysia's private higher education sector.